Peningkatan Keselamatan Kerja Pekerja Konstruksi Melalui Edukasi dan Pelatihan Penggunaan APD di Proyek Jembatan Bendungan Lau Simeme - Ginting, Evfy Septriani (INSTITUT KESEHATAN DELI HUSADA, 2025)
The construction sector carries a high risk of workplace accidents, especially when workers are not disciplined in using Personal Protective Equipment (PPE). To reduce potential hazards, this Community Service Program was implemented at the Lau Simeme Dam Bridge construction project, focusing on improving workers' understanding and skills through education and field practice. Activities included outreach, simulations on proper PPE use, and intensive mentoring to familiarize workers with safe work practices. Evaluations were conducted to assess changes in behavior and knowledge following the training. This program is expected to foster a safety-oriented work culture, reduce accident rates, and support increased construction workforce productivity.